Perioperative outcomes of interrupted anticoagulation in patients with non-valvular atrial fibrillation undergoing non-cardiac surgery - Bo Eun Park; Myung Hwan Bae; Hyeon Jeong Kim; Yoon Jung Park; Hong Nyun Kim; Se Yong Jang; Jang Hoon Lee; Dong Heon Yang; Hun Sik Park; Yongkeun Cho; Shung Chull Chae (Yeungnam University Journal of Medicine, 2020)
Background This study aimed to investigate the incidences of and risk factors for perioperative events following anticoagulant discontinuation in patients with non-valvular atrial fibrillation (NVAF) undergoing non-cardiac surgery. Methods A total of 216 consecutive patients who underwent cardiac consultation for suspending perioperative anticoagulants were enrolled. A perioperative event was defined as a composite of thromboembolism and major bleeding. Results The mean anticoagulant discontinuation duration was 5.7 (±4.2) days and was significantly longer in the warfarin group (p<0.001). Four perioperative thromboembolic (1.9%; three strokes and one systemic embolization) and three major bleeding events (1.4%) were observed. The high CHA2DS2-VASc and HAS-BLED scores and a prolonged preoperative anticoagulant discontinuation duration (4.4±2.1 vs. 2.9±1.8 days; p=0.028) were associated with perioperative events, whereas the anticoagulant type (non-vitamin K antagonist oral anticoagulants or warfarin) was not. The best cut-off levels of the HAS-BLED and CHA2DS2-VASc scores were 3.5 and 2.5, respectively, and the preoperative anticoagulant discontinuation duration for predicting perioperative events was 2.5 days. Significant differences in the perioperative event rates were observed among the four risk groups categorized according to the sum of these values: risk 0, 0%; risk 1, 0%; risk 2, 5.9%; and risk 3, 50.0% (p<0.001). Multivariate logistic regression analysis showed that the HAS-BLED score was an independent predictor for perioperative events. Conclusion Thromboembolic events and major bleeding are not uncommon during perioperative anticoagulant discontinuation in patients with NVAF, and interrupted anticoagulation strategies are needed to minimize these.